1998
DOI: 10.1271/bbb.62.2177
|View full text |Cite
|
Sign up to set email alerts
|

N2733, 1-[3-(3-Pyridyl)-acryloyl]-2-pyrrolidinone Hydrochloride Inhibits LPS-induced TNF-α Production and Improves Survival in Endotoxemic Mice

Abstract: N2733, 1-[3-(3-pyridyl)-acryloyl]-2-pyrrolidinone hydrochloride, was examined for its effect on TNF-alpha production by human myeloid THP-1 cells stimulated with lipopolysaccharide (LPS). N2733 inhibited LPS-induced release of TNF-alpha from THP-1 cells with an IC50 of 11 microM. N2733 did not affect the cell viability at the concentration of 50 microM or 100 microM. This indicates that N2733 is a potent inhibitor for TNF-alpha production without severe cytotoxicity. N2733 was also studied in two murine endoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Several studies have reported that pyrrolidinone derivatives have anti-inflammatory activities (9-11). Rolipram, a type 4 phosphodiesterase inhibitor, and N2733, a pyridyl acryloyl pyrrolidinone, inhibits LPS-induced NF-κB activation (9)(10)(11). Previously, we also demonstrated that the fumaryl pyrrolidinone derivate, IPOP, inhibits TLR2 and TLR4 agonist-induced NF-κB activation and COX-2 expression (8).…”
Section: Ipop Does Not Inhibit Activation Of Irf3 Induced By Downstrementioning
confidence: 99%
“…Several studies have reported that pyrrolidinone derivatives have anti-inflammatory activities (9-11). Rolipram, a type 4 phosphodiesterase inhibitor, and N2733, a pyridyl acryloyl pyrrolidinone, inhibits LPS-induced NF-κB activation (9)(10)(11). Previously, we also demonstrated that the fumaryl pyrrolidinone derivate, IPOP, inhibits TLR2 and TLR4 agonist-induced NF-κB activation and COX-2 expression (8).…”
Section: Ipop Does Not Inhibit Activation Of Irf3 Induced By Downstrementioning
confidence: 99%
“…Activation of this transcription factor then induces the expression of pro-inflammatory gene products including COX-2 13 . It has been reported that pyrrolidinone derivatives have anti-inflammatory activities [14][15][16] . Rolipram, a type 4 phosphodiesterase inhibitor, inhibits LPS-induced NF-κB activation and E-selectin, TNF-α, and IL-6 expression 14 .…”
Section: Ipop Suppresses Agonist-independent Nf-κb Activation Mediatementioning
confidence: 99%
“…Rolipram, a type 4 phosphodiesterase inhibitor, inhibits LPS-induced NF-κB activation and E-selectin, TNF-α, and IL-6 expression 14 . N2733, a pyridyl acryloyl pyrrolidinone, inhibits LPS-induced TNF-α production and IL-1β-induced NF-κB activation and iNOS expression 15,16 . These results suggest that pyrrolidinone derivatives exert their anti-inflammatory activity by regulating the TLR4 signaling pathway.…”
Section: Ipop Suppresses Agonist-independent Nf-κb Activation Mediatementioning
confidence: 99%
“…They are expressed in variable levels among different tissues and their expression is regulated by various physiological and pathological stimuli [5], providing an additional level of regulation in prostaglandin signaling. For example, LPS treatment highly induced the expressions of EP2 and EP4 receptors [6, 7] in macrophages and these inductions were suggested to be involved in the regulation of TNF-α [8]. In addition, the overexpression of the EP2 receptor in the epidermis of EP2 transgenic mice resulted in enhanced skin tumor formation, proliferation, and blood vessel formation [9].…”
Section: Introductionmentioning
confidence: 99%